Dimensões do bulbo úmido em solo arenoso, em função de diferentes vazões e tempos de aplicação de água - Alves, Daniel Soares (2010)
The drip irrigation prompt application of water makes it possible to obtain a very high efficiency of water use, provided it is properly scaled. There are several factors that directly interfere in the movement of soil water, some factors influence the way that the wet bulb takes. Some are from the soil itself, such as soil texture, soil density and structure, among others. Others are related to the system itself, such as flow rate of emitters, positioning them in relation to the soil surface, time and volume of water application. Stevia is a culture that has gained over the years, promising markets in terms of non-caloric sugars, industrially extracted from its leaves, to be added in food and beverage products mainly. This work was conducted at the State University of Maringá (UEM) aiming to seek evidence for the correct sizing of drip irrigation systems for stevia cultivation in sandy soil in the region of northwest in Paraná state. Thus, the soil was packed in containers, in which TDR probes were installed. These cases were subjected to frequent irrigations during a period of 8.0 consecutive hours, with emitters of different flow rates (1.0, 2.0, 4.0, 6.0, 8.0 Lh-1) arranged on the surface and subsurface (0.15 m depth). The presented results allowed evaluating the dimensions of wet bulb in the soil. In treatments in which the transmitter was on the surface, the ideal saturated disk for meeting the needs of the culture was formed at 4.5, 3.0, 2.5 and 0.5 hours for the flow rates of 1.0, 2, 0, 4.0, 6.0, 8.0 Lh-1, respectively, after the beginning of water application. When the used emitter was in the subsurface, these little values differed for the flow rates of 1.0, 2.0, 4.0 Lh-1, but for the flow rates of 6.0 and 8.0 Lh-1 this condition was met 3.0 hours after the beginning of the irrigation, being characterized by large losses of water mainly in depth. The obtained results showed that the studied combinations between flown application and the position of the emitters, allow the identification of a combination that is suitable for designing the system of drip irrigation for the stevia cultivation, respecting the culture characteristics, in terms of spacing and water demand. It is also concluded that flows up to 4.0 Lh-1 are more appropriate, particularly with located transmitter on the surface. Use of higher flow rates, particularly with buried transmitters, has great potential to promote unacceptable percolation losses and therefore should be avoided.